Coexistir na fronteira: notas de um antropólogo sobre a trajetória de um grupo de jovens em meio a uma guerra entre a comunidade e o tráfico de drogas - Fonseca, Mário (2009)
On behalf of an anthropology that looks for to analyze the can-resistance relationships starting from the coexistence among the several components inside of different urban territories and that he seeks to do to emerge the several present violence forms in the daily relationships is that I intended to accomplish this research. In my entitled research of Master's degree of Cartography of the resistances: an anthropological analysis of the Pavilion Eight of the House of Detention of São Paulo where I inferred that such sociability can also be understood as being the product of an intriguing political game between the detainees and the forces of the State, generating hierarchization of the involved subjects, nets of corruption and extortion, and finally criminal cells, where not only they will make part detainees, but also those that should reeducate them. Looking for new prisms for the discussion of the urban violence, I intend in that doctorate research to give continuity and to problematize as she felt the sociability change among a group of young called pichadores Korja, considered rebellious, of the Vila Brasilândia and the community in the which they lived. I understand that the youths residents' of the outlying neighborhoods of the great cities coexistence is built, in general in the street, the corners become encounter points and leisure. It is there that you build the friendships and the youths look for to build collective identities, at the same time in that they learn how to live together with the urban violence and to work with the repressive apparels. In what he says respect, more specifically to these young of the Vila Brasilândia, what wakes up my interest is to understand as she felt the transformation so much of the sociability, as in the way that the community noticed them. If at the beginning this she saw them as that that in fact were, rebellious and dreamer youths, little by little passed to be seen as dangerous individuals and indesejados that there were if transformed in a problem and in a weight for the community. That change felt progressively, starting from the moment in that they passed to be allured by the traffic that looked for to dominate the community. In a first moment those young ones saw each other in the center of a crossed fire, where on one side, the community tried cooptá-los and to recover them through practices normalizadoras, and of the other, the traffickers that you tried to seduce them and to allure them, fact that frequently finished with the death of some of them